2016
DOI: 10.1186/s13046-016-0295-1
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting cytotoxic T lymphocytes against human laryngeal cancer-derived antigens: evaluation of dendritic cells pulsed with a heat-treated tumor lysate and other antigen-loading strategies for dendritic-cell-based vaccination

Abstract: BackgroundDendritic cells (DCs) have been used successfully in clinical pilot studies. However, tumor-specific immunity and clinical responses were only induced in certain cancer patients. It has been well documented that immunotherapy efficacy can be optimized for responses using antigen pulsing.MethodsThe human laryngeal squamous cell cancer (LSCC) cell line SNU899 was used to evaluate the in vitro anti-tumor efficacy of three different preparations of dendritic cell (DC) vaccines consisting of either whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Based on this classification of human Tregs, our study provided evidence to support the notion of heterogeneous Treg subsets in HNSCC patients ( Sun et al , 2014 , 2015, 2016 , ). We showed that aTreg cells, as the predominant cell population among tumour-infiltrating Foxp3 + Treg cells, accelerate disease progression by suppressing TAA immunity in patients with HNSCC ( Sun et al , 2016 ; Wei et al , 2016 ). To determine whether TSN-exposed M2-like macrophages contribute to an increase in aTreg cells, we analysed the subsets of induced Treg cells.…”
Section: Discussionmentioning
confidence: 95%
“…Based on this classification of human Tregs, our study provided evidence to support the notion of heterogeneous Treg subsets in HNSCC patients ( Sun et al , 2014 , 2015, 2016 , ). We showed that aTreg cells, as the predominant cell population among tumour-infiltrating Foxp3 + Treg cells, accelerate disease progression by suppressing TAA immunity in patients with HNSCC ( Sun et al , 2016 ; Wei et al , 2016 ). To determine whether TSN-exposed M2-like macrophages contribute to an increase in aTreg cells, we analysed the subsets of induced Treg cells.…”
Section: Discussionmentioning
confidence: 95%
“…Another interesting preclinical approach is the usage of tumour cell lysates [ 173 ]. In this study, DCs pulsed with heat-treated tumour cell lysates of laryngeal cancer could induce anti-tumour immunity against a cell line.…”
Section: Tumour-associated Antigens (Taas)mentioning
confidence: 99%
“…The principle of DC vaccine preparation is to collect lymphocytes from peripheral blood, induce them into DC in vitro, and present tumor antigens to DCs, thereby providing a large number of these cells for active immunotherapy (Dannull et al, 2013). Tumor antigen presentation to DC can be accomplished in a variety of ways (Osada et al, 2015;Wei et al, 2016). A new method was developed to present autologous tumor antigens to the cytoplasm of DCs.…”
Section: Discussionmentioning
confidence: 99%